Practice before policy? Unpacking the black box of progressive teaching in Swedish secondary schools. Issue 4 (4th July 2021) - Samuelsson, Johan; Gericke, Niklas; Olin-Scheller, Christina; Melin, Åsa
ABSTRACT: The aim of the article is to deepen the knowledge of progressivism and how it was manifested in practice in Swedish secondary schools from a teacher perspective before it was prescribed in policy during the reforms of the 1950s. In the current educational debate, progressivism is blamed by some for being the root of a permissive style of education in decline that no longer provides any knowledge to students, and regarded by others as the starting point for the modern form of democratic schooling. The question we pursue is in what way progressive teaching practice existed before policy. We do that by investigating teacher narratives describing their own teaching practices found in a historical archive from 1946. Hence, rather than looking at the policy level as in most studies, we are unpacking the black box of progressive teaching. Through thematic analysis, we investigate 209 secondary teacher narratives from teachers of History, Biology and Mother tongue. We found that the theme of student participation was very frequently reported in 76% of the accounts, while student interaction (33%) and extended classroom (37%) were somewhat less reported. Hence, our study shows that progressive teaching existed in different ways before it appeared in policy.